The Influence of Index Card Match on Mathematics Learning Outcomes in Inverse Matrix Material in High School - Hasrini Jufri; Latri Aras (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2024)
Lack of interest in learning inverse matrix mathematics causes a lack of interest in learning mathematics and produces unsatisfactory results. Researchers tried to conduct experimental research on the application of the Index Card Match learning model to mathematics learning outcomes in Inverse Matrix material at SMA Negeri 21 Makassar. The approach used is a quantitative approach with a pre-experimental method with a One Group Pretest Posttest design. The data collection techniques used are tests, observation, interviews and documentation. Meanwhile, data analysis uses the normality test and the Simple Paired T-Test hypothesis test. The results of this research were hypothesis testing on the pretest and posttest which obtained results of 0.000 < 0.05. H0 was rejected and Ha was accepted. From these results, it means that the application of the Index Card Match model has an influence on cognitive mathematics learning outcomes in inverse matrix material for class XI students at SMA Negeri 21 Makassar..